Whole-Genome Metagenomic Analysis of Functional Profiles in the Fecal Microbiome of Farmed Sows with Different Reproductive Performances - Hiroto Miura; Takamitsu Tsukahara; Ryo Inoue (Microorganisms)
Recent studies suggested an association between the reproductive performance of sows and their gut microbiota. To understand how the gut microbiota affect the reproductive performances of sows, we conducted a whole-genome metagenomic analysis on the fecal microbial functional profiles of sows with high and low reproductive performances. We used 60 sows from six farms (10 sows/farm), including 30 sows from three farms with higher reproductive performances (the mean number of weaned piglets/sow/year) (group H) and 30 sows from three farms with lower performances (group L). Fecal microbial DNA was subjected to a whole-genome metagenomic analysis. Biomarker exploration analysis identified “carbohydrate transport and metabolism” as the most discriminative function enriched in group H. Further analysis of carbohydrate-active enzymes revealed that the fecal microbiome of group H had a greater capacity to degrade dietary fiber, specifically cellulose and pectin. Group H also exhibited higher fecal short-chain fatty acid (SCFA) concentrations than group L, with the abundances of cellulose- and pectin-degrading genes showing significant positive correlations with fecal SCFA concentrations. Taxonomic analysis indicated greater contributions of Prevotella, Treponema, Ruminococcus, and Fibrobacter to cellulose and pectin degradation in the fecal microbiome in group H. In conclusion, higher reproductive performances of sows were, at least in part, associated with a greater microbial capacity for degrading cellulose and pectin, resulting in a higher SCFA production in the hindgut.